4(x-3)+2=26

Simple and best practice solution for 4(x-3)+2=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+2=26 equation:


Simplifying
4(x + -3) + 2 = 26

Reorder the terms:
4(-3 + x) + 2 = 26
(-3 * 4 + x * 4) + 2 = 26
(-12 + 4x) + 2 = 26

Reorder the terms:
-12 + 2 + 4x = 26

Combine like terms: -12 + 2 = -10
-10 + 4x = 26

Solving
-10 + 4x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 4x = 26 + 10

Combine like terms: -10 + 10 = 0
0 + 4x = 26 + 10
4x = 26 + 10

Combine like terms: 26 + 10 = 36
4x = 36

Divide each side by '4'.
x = 9

Simplifying
x = 9

See similar equations:

| 7m+n=2forn | | 16x-8=14x+8 | | -3-(2-3x)=2x-(5-x) | | (3x-c)-5=x-7 | | 13-2n=-37 | | a+b(x-y)=cforx | | 20x+10=50 | | 2(x+4)-5(2x-1)= | | 11x-3=10x+5 | | n^2+n=6 | | 12-1.2(x-5)=22-2(5-3s) | | 2x+3/3=x-1/x-2 | | 3+(9n+5)=35 | | 5x+9x+2x+20=52 | | Ax+by=cforx | | n=300 | | 21-(x-5)=-4x+12 | | 3-7x=10-(x+1) | | 3/2u+3/8=5/4+9/2u | | 7+12x=115 | | 7+12x=105 | | 12x-(-2x+9)=26 | | 8u-6=9u-9 | | -10-(5x+2)=8 | | x+71=60 | | -8m-38=5(1-4m)-7 | | 1035/42 | | -3(3s-6)-18=-3(5s+0)-5 | | 3(3v-1)=6v-2 | | 4x-4=x+(17-4x) | | 10x+70=180 | | 6b=8(b-7) |

Equations solver categories